Joint Goals in Older Couples: Associations With Goal Progress, Allostatic Load, and Relationship Satisfaction - Ungar, Nadine; Michalowski, Victoria I.; Baehring, Stella; Pauly, Theresa; Gerstorf, Denis; Ashe, Maureen C.; Madden, Kenneth M.; Hoppmann, Christiane A. (Frontiers in Psychology, 2021)
Older adults often have long-term relationships, and many of their goals are intertwined with their respective partners. Joint goals can help or hinder goal progress. Little is known about how accurately older adults assess if a goal is joint, the role of over-reporting in these perceptions, and how joint goals and over-reporting may relate to older partners' relationship satisfaction and physical health (operationally defined as allostatic load). Two-hundred-thirty-six older adults from 118 couples (50% female; Mage=71 years) listed their three most important goals and whether they thought of them as goals they had in common with and wanted to achieve together with their partner (self-reported joint goals). Two independent raters classified goals as "joint" if both partners independently listed open-ended goals of the same content. Goal progress and relationship satisfaction were assessed one week later. Allostatic load was calculated using nine different biomarkers. Results show that 85% self-reported at least one goal as joint. Over-reporting– the perception that a goal was joint when in fact it was not mentioned among the three most salient goals of the spouse – occurred in one-third of all goals. Multilevel models indicate that the number of externally-rated joint goals was related to greater goal progress and lower allostatic load, but only for partners with little over-reporting. More joint goals and higher over-reporting were each linked with more relationship satisfaction. In conclusion, joint goals are associated with goal progress, relationship satisfaction, and health, but the association is dependent on the domain of functioning.